Substantial decreases of light absorption, concentrations and relative contributions of fossil fuel to light-absorbing carbonaceous aerosols attributed to the COVID-19 lockdown in east China. (15th April 2021) - Lin, Yu-Chi; Zhang, Yan-Lin; Xie, Feng; Fan, Mei-Yi; Liu, Xiaoyan
Abstract: To prevent spreads of Coronavirus disease-2019 (COVID-19), China adopted the lockdown measures in late January 2020, providing a platform to study the response of air quality and atmospheric chemical and physical properties to strict reduced emissions. In this study, the continuous measurements of aerosol light absorption were conducted in Nanjing, east China, from January 3 to March 31, 2020. Our results showed that the contribution of black carbon (BC) to light absorption at the different wavelengths was more than 75% and the rest light absorption was contributed by brown carbon (BrC), which was mainly originated from primary emissions. Secondary BrC absorption, which was mainly produced by photochemical oxidation, constituted a minor fraction (2–7%) of the total absorption. Compared with the sampling in the pre-lockdown, the significant decreases of BC (43%) and secondary BrC absorption (31%) were found during the lockdown period, resulting in a substantial decrease of solar energy absorbance by 36% on a local scale. The control measures also changed the diurnal variations of light absorption. Due to the reduced emissions, the relative fraction of fossil fuel to BC also dropped from 78% in the pre-lockdown to 71% in the lockdown. The concentrations of BC, PM2.5 and NO2 decreased 1.1 μg m −3, 33 μg m −3 and 9.1 ppb whereas O3 concentration increased 9.0 ppb during the COVID-19 lockdown period. The decreased concentrations of BC, PM2.5 and NO2 were mainly contributed by both emission reduction (51–64%) and meteorological conditions (36–49%). Our results highlighted that the balance of control measures in alleviation of particulate matter (PM) and O3 pollution, and meteorology should be seriously considered for improvement of air quality in this urban city of China. Graphical abstract: Image 1 Highlights: BrC accounted for 25% of the total light absorption at wavelength of 330 nm. Secondary BrC absorption was mainly contributed by photochemical oxidation. Reduced emissions decreased the solar energy absorbance by 36% on a local scale. BC, PM2.5 and NO2 decreased by 41, 57 and 51%, respectively, during the lockdown. Decreased NOx emissions enhanced O3 by 50%. Abstract : Reduced emissions decreased the concentrations of primary pollutants, aerosol light absorption and solar energy absorbance, but increased O3 levels on a local scale.